2019
DOI: 10.1002/pssa.201900172
|View full text |Cite
|
Sign up to set email alerts
|

Fundamental Characteristics of Cyanide‐Related Multielement Molecular Ion‐Implanted Epitaxial Si Wafers for High‐Performance CMOS Image Sensors

Abstract: Fundamental characteristics such as metal‐gettering capability and defect morphology of a cyanide‐related multielement molecular (CH4N) ion‐implanted epitaxial silicon (Si) wafer are investigated. It is found that the CH4N ion‐implanted epitaxial Si wafer has a higher gettering capability for transition metallic impurities than a hydrocarbon molecular (C3H5) ion‐implanted epitaxial Si wafer. This higher metal‐gettering capability of the CH4N ion‐implanted epitaxial Si wafer may be due to the formation of stack… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…The authors showed that carbon atoms formed SiC precipitates, whereas oxygen or nitrogen atoms are responsible mainly for the extended defect formation. [ 6–10 ] They did not investigate the oxygen or nitrogen atom roles in the silicon oxide and nitride gettering properties.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The authors showed that carbon atoms formed SiC precipitates, whereas oxygen or nitrogen atoms are responsible mainly for the extended defect formation. [ 6–10 ] They did not investigate the oxygen or nitrogen atom roles in the silicon oxide and nitride gettering properties.…”
Section: Introductionmentioning
confidence: 99%
“…[5] Further improvement of epilayer properties has been demonstrated recently by the multielement molecular ion implantation in Cz-Si wafers before the thick epitaxial layer overgrowth. [6][7][8][9][10] These authors implanted molecular hydrocarbon (C x H y ), methyloxidanyl (CH 3 O), or cyanide (CH 4 N) molecular ions at moderate fluences (1-5) Â 10 15 cm À2 as the related multielement gettering layers. They proved successful gettering in the implanted layers of not only metal impurities such as Fe or Cu, but even hydrogen atoms at 10 18 cm À3 concentration after silicon epitaxial layer overgrowth and furnace annealing at 1100 C. The authors showed that carbon atoms formed SiC precipitates, whereas oxygen or nitrogen atoms are responsible mainly for the extended defect formation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…33 In the CH 3 O-ion-implanted epitaxial Si wafers, in addition to C x Si y precipitates, dislocation loops lying on the {111} planes are formed in the ion projected range. 32,34 Hence, the most significant difference between the CH 3 O-ion-implanted and hydrocarbon-molecular-ion-implanted epitaxial Si wafers is whether or not the extended defects are generated. The generation of dislocation loops in a multielement-molecular-ionimplanted Si wafer is attributed to the including of O atoms in the molecular ion.…”
mentioning
confidence: 99%
“…21 In addition, for further enhancement of the CIS performance, we have been developing a novel functional CH 4 N-molecular-ion-implanted epitaxial Si wafer. 22 The CH 4 N ion implantation technique enables the implantation of nitrogen (N) in addition to H and C. The CH 4 N-ion-implanted epitaxial Si wafer has a high density of EOR defects as well as C x Si y precipitates in the ion projected range. 22 We previously demonstrated that the CH 4 N-ion-implanted epitaxial Si wafer also has a high gettering capability for metals and light element impurities (H, C, N, and O).…”
mentioning
confidence: 99%